The adequacy of wealth among those approaching retirement - Rowena Crawford; Cormac O'Dea (Institute for Fiscal Studies (IFS), 2012)
There has been ongoing concern in many quarters in recent decades that individuals in the UK are not saving enough to provide themselves privately with an adequate income in retirement. A number of long-run trends have acted to make it harder for individuals to accumulate sufficient resources, including unexpectedly rapidly increasing life expectancies and the reduced availability of defined benefit (DB) pensions in the private sector. The Pensions Commission was appointed in 2002 with the remit of 'keeping under review the adequacy of private pension saving in the UK, and advising on appropriate policy changes', and its first report (Pensions Commission, 2004) projected that many people, particularly those with defined contribution (DC) pensions, would have 'inadequate' resources in retirement...
Keywords: 330